Becoming at the boundaries of language: Dramatic Enquiry for intercultural learning in UK higher education. (2nd November 2019) - Harvey, Lou; McCormick, Brad; Vanden, Katy
ABSTRACT: This article reports on a co-produced project introducing an innovative, drama-based method for enhancing UK HE students' intercultural learning. We ran two workshops for a mixed cohort of students and demonstrate in our analysis how these decentred language as the chief vehicle of communication, treating language as one of many materials in the communicative assemblage. This facilitated new ways of knowing-through-being for the participants, which enabled them to move across perceived intercultural boundaries and to bring new boundaries into existence in an ongoing process of becoming . We offer this analysis as grounds for a more ethical internationalisation of higher education.